2012
DOI: 10.1163/187847612x646776
|View full text |Cite
|
Sign up to set email alerts
|

A neural link between feeling and hearing

Abstract: Hearing and feeling both rely upon the transduction of physical events into frequency-based neural codes, suggesting that the auditory system may be intimately related to the somatosensory system. Here, we provide evidence that the neural substrates for audition and somatosensation are anatomically linked. Using diffusion tensor imaging with both deterministic and probabilistic tractography to measure white matter connectivity, we show that there are extensive ipsilateral connections between the primary audito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 47 publications
(66 reference statements)
1
16
0
Order By: Relevance
“…abnormalities of function were associated, for the majority of the areas, with abnormalities of structure within the visual and auditory cortices. A recent single-case study showed extensively increased structural connections between the auditory and secondary somatosensory cortex in the lesioned hemisphere of a patient with acquired auditory-tactile synesthesia [Ro et al, 2012].…”
Section: Figurementioning
confidence: 99%
“…abnormalities of function were associated, for the majority of the areas, with abnormalities of structure within the visual and auditory cortices. A recent single-case study showed extensively increased structural connections between the auditory and secondary somatosensory cortex in the lesioned hemisphere of a patient with acquired auditory-tactile synesthesia [Ro et al, 2012].…”
Section: Figurementioning
confidence: 99%
“…However, some supporting human evidence is found in prior reports. Ro, Ellmore, and Beauchamp (2013) used DTI and showed direct connectivity in humans between primary auditory cortex and primary somatosensory cortex. Eickhoff et al (2010) showed both structural and functional connections between primary motor cortex and operculum parietal (OP) 4, and functionally linked OP 4 to more basic sensorimotor as opposed to somatosensory processing.…”
Section: Structural Connectivitymentioning
confidence: 99%
“…Anecdotally, there are a number of widely experienced sensations that appear to involve both audition and touch (e.g., the physical sensation on your skin from hearing nails scratching on a chalkboard or an insect buzzing; Kitagawa & Spence, 2006). Supporting this observation, there is also evidence of a patient with a form of synaesthesia that results in auditory stimuli producing tactile sensations (Ro, Ellmore, & Beauchamp, 2013). This patient has a right ventrolateral thalmic lesion, which deprives her somatosensory cortex of normal somatosensory input.…”
mentioning
confidence: 91%